Validity and Reliability of the Dyslexia Checklist for Chinese Children - Hou, Fang; Qi, Ling; Liu, Lingfei; Luo, Xiu; Gu, HuaiTing; Xie, Xinyan; Li, Xin; Zhang, Jiajia; Song, Ranran (Frontiers in Psychology, 2018)
The study on developmental dyslexia (DD) was fairly mature in past decades. However, there has been lack of a standardized and convenient instrument for screening Chinese dyslexia. The purpose of this study was to assess the reliability and validity of the Dyslexia Checklist for Chinese Children (DCCC), which was administered to Chinese students in grades 2 through 6 of primary school. A total of 545 students from grades 2 through 6 in Wuhan were recruited to participant in this study. We used Confirmatory Factor Analysis (CFA) to evaluate the structure validity of the DCCC. Concurrent validity was determined by the correlations between DCCC and the verbal comprehension index, Chinese achievement and mathematical ability. Reliability of the DCCC was assessed by the test-retest reliability and internal consistency. CFA suggested that the first order model with eight factors and 54 items fit the data well after discarding item 5 (RMSEA=0.054, CFI=0.941, TLI=0.937). The DCCC was negatively associated with verbal comprehension (r=-0.241), Chinese achievement (r=-0.390) and mathematical ability (r=-0.346). The test-retest reliability of DCCC was 0.759, and the internal consistency of all subscales was above 0.758. The DCCC proved to have adequate validity and reliability to screen Chinese dyslexia among the students in grades 2 through 6.